K problematice hry: Příklad pubertální třídy - Kučera, Miloš (Lidé města, 1999)
Generally, game is considered in an undifferentiated way as a good, simply positive thing and it is glorified a a sign of freedom and creativity. Professional literature, too, included moral assessment of the game, both for the life of an individual and the development of civilisation, but it is much more sophisticated (see the work by J. Huizinga and R. Caillois). Caillois uses two criteria: the value of various principles of the game, and the observation of the borders of the game itself or its definition in usual or normal life. Ad 1: In his view our civilisation is characterised by a transition from archaic principles of the mimicry (especially as mask) and ilinx (such as vertigo) to modern agon (competition, credentials) and alea (dice, accident); these principles are social mechanisms and institutions (e.g., agon is competition and alea stock exchange), not only games in the narrow sense (e.g., not only sport or roulette); however, certain games fit in certain social mechanisms, react to a given "normal life" and there is interdependence with them. Ad 2: this interdependence is in order - it is neiter a corruption or perversion of the game. Caillois is afraid that this might affect an individual if the game starts to overlap in life, replace it and decline in it - proper competition turns into uncontrolled violence and deviousness and betting on something into superstition in everything. As a result, the moral approach to a game is very rigid. The writer has tried to explain through games the main issue of the life of a 5th-6th school class: whether sex can materialise and related horror. He called sexual games, rituals and habits with game aspect waves (as at stadiums): (a) transgressive: thanks to the aspect "as if" or "just like" they allow to proceed farther in direct sexual behaviour (mass waves of teasing, reminiscent of an orgy or a dream about an orgy), in love choices and gestures of a couple ("social games", mostly in a selected amorous group with the function of declaring or publishing love; the division of the group into couples; anticipation or divination of a love object) or in the articulation of sex fantasies (pornographic production); (b) the French le charivari, English rough music: the community mocks love itself as a transgression or potential crime - after the suffering mockers dismiss the couple; (c) a wave of purification: accumulated sins, including sexual and erotic ones, are symbolically summarised into a gesture of "tagging" someone in a chase (while the name of an infectious disease or a pupil is said). This means an evident smearing or purification. The example of a class shows that it is necessary to conceive the borders of a game (or life, environment) as it is to be used by the community; however, it is difficult to morally denounce it if the game is transgressed, corrupted or perverted. The members of the community use the help of artificia dirt - it is a sign of superstition or perversion of alea? When teasing girls, boys use masks (the category of mimicry) of hunters of female bodies (agon) and avoid frontal encounter with a rival in love. However, the games serve not only to restrict the dimension of normal life, but also prepare the openess of its sector in adult life. The interdependence game-life and games among themselves has various forms as revealed by the function of the system of games. As already written by Caillois, many of the archaic forms are still surviving in some form at present.